To solve the factored quadratic equation \( 0 = -13x(x - 6) \), we can start by setting the equation equal to zero:
\[ -13x(x - 6) = 0 \]
This equation will be true if either factor is zero. Thus, we can set each factor equal to zero:
- \( -13x = 0 \)
- \( x - 6 = 0 \)
Solving the first factor:
\[ -13x = 0 \implies x = 0 \]
Solving the second factor:
\[ x - 6 = 0 \implies x = 6 \]
Thus, the solutions to the equation are:
\[ x = 0 \quad \text{and} \quad x = 6 \]
Therefore, the solution set is
\[ {0, 6} \]
So the correct response is:
The solution set is \( x = {0, 6} \).